Multiple Complications of Congenital Cytomegalovirus Infections - Retayasa Retayasa; Hamid A.; Kari K. (Paediatrica Indonesiana, 1997)
Congenital cytomegalovirus (CMV) is the most frequently occurring viral infection of the newborn infants. Cytomegalovirus agent which commonly invades human early in life may cause a spectrum of clinical manifestations from asymptoÂmatic to severe congenitally infected newborn with multiorgan involvement. We report two cases of multiple complications of congenital cytomegalovirus infections admitted to the Department of Child Health Sanglah General Hospital. The diagnosis of congenÂital CMV infections was based on clinical and laboratory examinations. The manifesÂtations of congenital infections in the first case of a 5,5 month old Balinese girl were microcephaly, ventricular septal defect, auricular dysgenesis and rectovaginal fistula. The results of laboratory examination showed positive IgG anti CMV. The IgM anti CMV was absent. In the second case the manifestations were epilepsy, microcephaly, cerebral palsy with craniosynostosis and porencephaly. Laboratory examinations showed positive IgG anti CMV but negative IgM anti CMV. The IgM and IgG anti rubella, toxoplasma, and HSV2 were negative in both cases.